Instituciones en Ecuador: Propiedad de Tierras y Derechos de Propiedad como una Convención Social - Grijalva , Diego (2006)
In this paper we analyze the structure of land property and property rights in Ecuador. We develop a coordination-game model where the interaction of individuals of different social classes plays a central role and the concepts of both formal and informal institutions are incorporated. Under specific assumptions, the model shows why certain societies reach and remain in an inefficient equilibrium regarding their property rights structure. We present a condensed history of the structure of land property and property rights in Ecuador and show the relevance and applicability of the model. We argue that the necessary conditions for stabilizing in an inefficient equilibrium have been present in Ecuador throughout history.